IL-37 alleviates intervertebral disc degeneration via the IL-1R8/NF-κB pathway. Issue 5 (May 2023) - Li, S.; Pan, X.; Wu, Y.; Tu, Y.; Hong, W.; Ren, J.; Miao, J.; Wang, T.; Xia, W.; Lu, J.; Chen, J.; Hu, X.; et al.
Summary: Objective: Intervertebral disc degeneration (IDD) has been reported to be a major cause of low back pain (LBP). Interleukin (IL)-37 is an anti-inflammatory cytokine of the interleukin-1 family, which exerts salutary physiological effects. In this study, we assessed the protective effect of IL-37 on IDD progression and its underlying mechanisms. Methods: Immunofluorescence (IF) was conducted to measure IL-37 expression in nucleus pulposus tissues. CCK-8 assay and Edu staining were used to examine the vitality of IL-37-treated nucleus pulposus cells (NPCs). Western blot, qPCR, ELISA as well as immunohistochemistry were used to assess senescence associated secreted phenotype (SASP) factors expression; and NF-κB pathway was evaluated by western blot and IF; while IL-1R8 knock-down by siRNAs was performed to ascertain its significance in the senescence phenotype modulated by IL-37. The therapeutic effect of IL-37 on IDD were evaluated in puncture-induced rat model using X-ray, Hematoxylin-Eosin, Safranin O-Fast Green (SO), and alcian blue staining. Results: We found IL-37 expression decreased in the IDD process. In vitro, IL-37 suppressed SASP factors level and senescence phenotype in IL-1β treated NPCs. In vivo, IL-37 alleviated the IDD progression in the puncture-induced rat model. Mechanistic studies demonstrated that IL-37 inhibited IDD progression by downregulating NF-κB pathway activation in NPCs by activating IL-1R8. Conclusion: The present study suggests that IL-37 delays the IDD development through the IL-1R8/NF-κB pathway, which suggests IL-37 as a promising novel target for IDD therapy.